Garcinol suppresses RANKL‐induced osteoclastogenesis and its underlying mechanism. Issue 5 (23rd November 2018) - Jia, Yewei; Jiang, Jiawei; Lu, Xuanyuan; Zhang, Tan; Zhao, Kangxian; Han, Weiqi; Yang, Wanlei; Qian, Yu
Abstract: Osteoclasts (OCs) are multinuclear giant cells responsible for bone resorption, and an excessive bone resorption by OCs plays an important role in osteoporosis. Commonly used drugs for the treatment of osteoporosis have severe side effects. As such, identification of alternative treatments is essential. Garcinol, a polyisoprenylated benzophenone extracted from the fruit of Garcinia indica, has shown a strong antitumor effect through the nuclear factor‐κB (NF‐κB) and mitogen‐associated protein kinases (MAPK) signaling pathways. However, the role of garcinol in the osteoclastogenesis is still unclear. Here, we demonstrated that garcinol can inhibit the receptor activator of NF‐κB ligand (RANKL)‐induced osteoclastogenesis, osteoclastogenesis‐related gene expression, the f‐actin ring, and resorption pit formation. In addition, garcinol abrogated RANKL‐induced osteoclastogenesis by attenuating the degradation of the MAPK, NF‐κB, and PI3K‐AKT signaling pathway as well as downstream factors c‐jun, c‐fos, and NFATC1. In vivo, suppression of osteoclastogenesis by garcinol was evidenced by marked inhibition of lipopolysaccharide‐induced bone resorption. In conclusion, our data demonstrated that garcinol inhibited the RANKL‐induced osteoclastogenesis by suppressing the MAPK, NF‐κB, and PI3K‐AKT signaling pathways and thus has potential as a novel therapeutic option for osteolytic bone diseases. Abstract : Garcinol suppresses osteoclast (OCs) formation and function in vitro. Garcinol impairs the receptor activator for the nuclear factor‐κB ligand (RANKL)‐induced mitogen‐associated protein kinases (MAPK), nuclear factor‐κB (NF‐κB), and AKT signaling pathway. Garcinol suppresses osteolysis in vivo. Garcinol may be a new therapeutic option for osteolytic bone diseases